Analysis of The Influence of Digital Financial Literacy, Digital Platforms, Return and Accountability on Public Intention to Invest Outside Java - Murini; Widyatmoko; Muhammad Djauhari; Nurhaifa Idris; Amat Suroso (SEULANGA SYSTEM PUBLISHER, 2023)
Finding out which factors financial knowledge, accountability, returns, religion, and digital platforms have the biggest effects on investing interest is the goal of this study. The general public is the study's population. In this study, random sampling was the method of sampling. 200 data points made up the sample size for this study, which employed the Roscoe theory sampling technique. This study employs a quantitative research design. Software called SPSS was used in this study. Primary sources were gathered for this study via questionnaires, and secondary materials were gathered through documentation studies. The study's findings demonstrate how investment interest is simultaneously influenced by the following variables: digital platforms, returns, accountability, financial literacy, and religiosity. Interest in investing is unaffected by financial literacy. Accountability has no bearing on interest in investments. Investment interest is not influenced by religiosity. Interest in investing is unaffected by return. Investment interest is influenced by digital platforms. The digital platform variable is the main factor impacting investment interest in this study.